A Noble-Metal-Free Spintronic System with Proximity-Enhanced Ferromagnetic Topological Surface State of FeSi above Room Temperature - Hori, Tomohiro (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2022 Wiley-VCH GmbH.